2018
DOI: 10.1177/1077801218794307
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Intimate Partner Violence Victimization and Perpetration Among Sexual Minority Women: A Latent Class Analysis

Abstract: This study explored patterns of intimate partner violence (IPV) victimization and perpetration in 150 sexual minority women (SMW): 25.3% had been sexually victimized, 34% physically victimized, 76% psychologically victimized, and 29.3% suffered an IPV-related injury. A latent class analysis found four behavioral patterns: (1) minor-only psychological perpetration and victimization; (2) no IPV; (3) minor-severe psychological, physical assault, and injury victimization, and minor-only psychological, physical, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
22
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 56 publications
5
22
0
2
Order By: Relevance
“…Internalized homophobia, resulting from minority stress, is linked to IPV perpetration and victimization [66]. We found that SM-FSW by identity have higher odds of physical IPV compared to their heterosexual counterparts, aligning with previous research among a general SMW population [67,68], indicating unique vulnerability related to sexual minority status. Further, barriers to existing IPV services include a limited understanding of SM IPV, stigma, and systemic inequities [69].…”
Section: Discussionsupporting
confidence: 86%
“…Internalized homophobia, resulting from minority stress, is linked to IPV perpetration and victimization [66]. We found that SM-FSW by identity have higher odds of physical IPV compared to their heterosexual counterparts, aligning with previous research among a general SMW population [67,68], indicating unique vulnerability related to sexual minority status. Further, barriers to existing IPV services include a limited understanding of SM IPV, stigma, and systemic inequities [69].…”
Section: Discussionsupporting
confidence: 86%
“…In comparison to non-TGNC sexual minorities, in a study of lifetime prevalence of IPV among non-TGNC sexual minority men, participants reported as follows: 34.8% sexual abuse, 38.2% physical abuse, 69.7% psychological abuse, and 28.1% suffered an IPV-related injury (Goldberg-Looney, Perrin, Snipes, & Calton, 2016). Among a sample of non-TGNC sexual minority women, the following lifetime prevalence of IPV was reported: 25.3% sexually victimized, 34% physically victimized, 76% psychologically victimized, and 29.3% injured because of IPV (Sutter et al, 2019). These studies show similar patterns of IPV victimization (higher levels of psychological victimization and lower levels of IPV related injury), but with some differences which may require further investigation.…”
Section: Prevalence Of Ipv In the Tgnc Communitymentioning
confidence: 99%
“…LGBT (Badenes-Ribera et al, 2017;Murray, Mobley, Buford, & Seaman-DeJohn, 2007;Nunan, 2004;Kimmes et al, 2019), acresce ainda a existĂȘncia de mitos relacionados com os papĂ©is de gĂȘnero (a convicção de que os homens cometem agressĂ”es e as mulheres sĂŁo, impreterivelmente, vĂ­timas) (Badenes-Ribera et al, 2015; Barros et al, 2019;Dias, 2016; ISSN 1807-0310 Greenwood, Relf, Bu Huang, Pollack, Canchola, & Catania, 2002;Madera & Toro-Alfonso, 2005;Russell, Kraus, Chapleau, & Oswald, 2019) e com as dinĂąmicas de relacionamento dos casais homossexuais (e.g., papĂ©is igualitĂĄrios na dĂ­ade) (Nunan, 2004), assim como o estigma, a homofobia social e a discriminação (Sutter, Rabinovitch, Trujillo, Perrin, Goldberg, Coston, & Calton, 2018;Kimmes et al, 2019), vigentes na sociedade no que diz respeito ao ser homossexual e, consequentemente, Ă  existĂȘncia de violĂȘncia no seio de um casal homossexual (Badenes-Ribera et al, 2015;Greenwood et al, 2002;Madera & Toro-Alfonso, 2005). O presente estudo, uma vez que se foca na problemĂĄtica da violĂȘncia entre parceiros Ă­ntimos do mesmo sexo, tem como principal objetivo avaliar as porcentagens de prevalĂȘncia da violĂȘncia nos relacionamentos Ă­ntimos entre pessoas do mesmo sexo, somente gays e lĂ©sbicas, no contexto portuguĂȘs, relativamente Ă  violĂȘncia fĂ­sica, psicolĂłgica, sexual e socioeconĂŽmica, tanto na vertente de vĂ­tima quanto na vertente de perpetrador.…”
Section: Introductionunclassified